Opolští Slezané jakožto těžce vymezitelná hraniční národnost v Polsku - Szmejová, Maria (Lidé města, 2002)
In post-war Poland, the official image of Polish society was turned to the needs of Communist regime. For that purpose cultural diversity of Polish society was ignored. It was particularly depressing for the members of borderland groups that considerably differ from such a model. We can observe it in Opole Silesia. This part of Paland belonged for a long time to Germany. Although Opole Silesia is no longer a borderland area (due to a change in the borders), Silesians feature as a typical borderland group. It is generally accepted that in Silesians families, villages and local communities which as a whole remainded Polish, there are individuals who tended to assimilate German culture. Some of them have established the German minority in Poland. This has caused many political and emotional problems. Opole Silesia has-become uneasy for Polish and German societies.